Textiles Functionalized with Copper Oxides: A Sustainable Option for Prevention of COVID-19 - Román, Luz Esmeralda (2022)
COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and healthcare-associated infections (HAIs) represent severe problems in health centers and public areas. Polyester/cotton (PES/CO) blend fabrics have been functionalized with copper oxides on an industrial scale. For functionalization, the impregnation dyeing technique was applied. The functionalized samples were tested virologically against SARS-CoV-2 and human coronavirus (229E) according to ISO 18184-2019 and microbiologically against Escherichia coli (ATCC 25922) bacteria according to ASTM E2149-2013. The results show that the fabric functionalized with copper oxides inactivated both viruses after 30 min of exposure, presenting excellent virucidal activity against 229E and SARS-CoV-2, respectively. Furthermore, its inactivation efficiency for SARS-CoV-2 was 99.93% and 99.96% in 30 min and 60 min exposure, respectively. The fabric inhibited bacterial growth by more than 99% before and after 10 and 20 washes. In conclusion, 265 m of PES/CO fabric (wide 1.7 m) was functionalized in situ on an industrial scale with copper oxide nanoparticles. The functionalized fabric presented virucidal and bactericidal properties against SARS-CoV-2 and Escherichia coli.